2013
DOI: 10.4196/kjpp.2013.17.5.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D on Blood Pressure and Endothelial Function

Abstract: Vitamin D deficiency is prevalent, primarily due to limited sun exposure, which may be observed in urban areas, or as a result of modern lifestyles. Common myths about vitamin D persist, including that it is mostly obtained from the diet and is only essential for bone and mineral homeostasis. Nonetheless, advances in biomedical science suggest that vitamin D is a hormone that is integral to numerous physiologic functions in most cells and tissues. Therefore, abnormal vitamin D levels may contribute to health d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…One woman in early and eight women in late pregnancy did not have blood samples collected for various other reasons. Among the healthy women blood was sampled at 15 (range [10][11][12][13][14][15][16][17][18][19] weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One woman in early and eight women in late pregnancy did not have blood samples collected for various other reasons. Among the healthy women blood was sampled at 15 (range [10][11][12][13][14][15][16][17][18][19] weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Preeclampsia is characterized by hypertension and is a frequent cause of preterm delivery. Clinical studies have demonstrated an inverse relationship between vitamin D levels and the blood pressure outside pregnancy (15,16), a mechanism that has been linked to the renin-angiotensin-aldosterone system (16,17).…”
Section: Key Messagementioning
confidence: 99%
“…Chronic treatment with calcitriol has shown that hypertensive rats have decreased endothelium dependent vascular contraction, reduced quantities of reactive oxygen species, and diminished expression of cyclooxigenase-1 [73], which suggests that vitamin D directly confers a protective function against endothelial dysfunction [74]. …”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the 1,25(OH)2D3-VDR complex locates to the nucleus where it heterodimerizes with retinoic acid receptor (RXR). The 1,25(OH)2D3-VDR-RXR complex subsequently binds to response elements of vitamin D (VDRE) in the promoter region of target genes to stimulate RNA transcription and protein expression that mediates many diverse actions (Mandarino et al, 2015;Min, 2013;Wacker & Holick, 2013a). Such vitamin D-regulated gene expression occurs in a broad array of cells, including b-pancreatic, epidermal small intestine, hematopoietic, parathyroid gland, placental, renal tubular, vascular endothelial, and smooth muscle ones, plus cardiomyocytes, lymphocytes, myocytes, osteoblasts, and osteoclasts (Mandarino et al, 2015;Wacker & Holick, 2013a).…”
Section: Daytime Sunlight Vitamin D Health and Well-beingmentioning
confidence: 99%